Late-Onset Antibody Deficiency Due to Monoallelic Alterations in NFKB1 - Schröder, Claudia; Sogkas, Georgios; Fliegauf, Manfred; Dörk, Thilo; Liu, Di; Hanitsch, Leif G.; Steiner, Sophie; Scheibenbogen, Carmen; Jacobs, Roland; Grimbacher, Bodo; Schmidt, Reinhold E.; Atschekzei, Faranaz (Frontiers in Immunology, 2019)
Adult-onset primary immunodeficiency is characterized by recurrent infections, hypogammaglobulinemia and poor antibody response to vaccines. In this study, we have analyzed targeted gene panel sequencing results of 270 patients diagnosed with antibody deficiency and identified five disease causative variants in NFΚB1 in five unrelated families. We detected two single base pair deletions and two single base pair insertions, causing severe protein truncations and one missense mutation. Immunoblotting, lymphocyte stimulation, immunophenotyping and ectopic expression assays demonstrated the functional relevance of NFΚB1 mutations. Besides antibody deficiency, clinical manifestations included infections, autoimmune features, lymphoproliferation, lymphoma, Addison’s disease, type 2 diabetes and asthma. Although partial clinical penetrance was observed in almost all pedigrees, all carriers presented a deficiency in certain serum immunoglobulins and the majority showed a lack of memory B cells (CD19+CD27+). Among all tested genes, NFΚB1 alterations were the most common monoallelic cause of antibody deficiency in our cohort.